A review on Real Time Monitoring of Bridge by Using Sensor Technology with scour accumulation - Prof.Sayali Kokane, Dr.Pramod Jadhav (Mathematical Statistician and Engineering Applications, 2021)
Now a day’s bridges are important as per travel aspect since it make passing of river or a ground easier in the travel and transport. But the bridges may collapse anytime due to flood to the river or due to aging and lead to disaster. Hence it is important to monitor the bridge conditions every time. Such type of bridge is dangerous to travel or use. The people who are using the bridge, they may face the unpredictable situations due to damaging of bridges. Hence, continuously monitoring the bridges is necessary for the better health of bridge. In this proposed system, we can see real time monitoring of bridge where we can detect flood, crack detection, load on the bridge, by using different sensors. Here, sensors help us to give information about bridge conditions to alert the user. This system contains water level sensors, load sensor, jumping wire for providing the information about real-time condition of bridge. The user of bridge gets the alert about the bridge conditions via LCD screen, LED and Buzzer. These all sensors, wire and alert devices are connected to microprocessor Arduino Uno .This system make sure to provide alert to all users so that many people who are going to use the bridge get protected from biggest accidents. In this way this system is helpful to save the life of people.